Atmospheric Plasma Deposition of Methacrylate Layers Containing Catechol/Quinone Groups: An Alternative to Polydopamine Bioconjugation for Biomedical Applications. Issue 11 (25th March 2018) - Czuba, Urszula; Quintana, Robert; De Pauw‐Gillet, Marie‐Claire; Bourguignon, Maxime; Moreno‐Couranjou, Maryline; Alexandre, Michael; Detrembleur, Christophe; Choquet, Patrick
Abstract: Bioconjugation of enzymes on coatings based on polydopamine (PDA) layers is an appealing approach to control biological responses on biomedical implant surfaces. As alternative to PDA wet deposition, a fast, solvent‐free, and dynamic deposition approach based on atmospheric‐pressure plasma dielectric barrier discharge process is considered to deposit on metallic surfaces acrylic‐based interlayers containing highly chemically reactive catechol/quinone groups. A biomimetic approach based on covalent immobilization of Dispersin B, an enzyme with antibiofilm properties, shows the bioconjugation potential of the novel plasma polymer layers. The excellent antibiofilm activity against Staphylococcus epidermidis is comparable to the PDA‐based layers prepared by wet chemical methods with slow deposition rates. A study of preosteoblastic MG‐63 human cell line viability and adhesion properties on plasma polymer layers demonstrates early interaction required for biomedical applications. Abstract : Enzyme conjugation of plasma polymer layers is presented as an attractive approach toward bacterial biofilm dispersal on metallic implant surfaces. Atmospheric‐pressure plasma copolymerization of al ‐3, 4‐dihydroxyphenylalanine monomer derivative allows the fast deposition of biocompatible and functional layers. Their bioconjugation with Dispersin B not only provides an additional Staphylococcal antibiofilm forming activity but also modifies osseointeractions, showing spreading of human preosteoblastic MG‐63 cells.